Soluble Interleukin-2 Receptor Level as a Marker of Hemophagocytic Lymphohistiocytosis in Children With Severe Dengue - Singh, Dhirendra; Raghunathan, Veena; Dhaliwal, Maninder; Rastogi, Neha; Chadha, Ritu; Yadav, Satya Prakash (Frontiers in Pediatrics, 2021)
Dengue induced-hemophagocytic lymphohistiocytosis (HLH) is increasingly recognized as an important cause of secondary HLH. Early identification of dengue HLH and directed therapy for HLH may help to alter the outcomes in critically ill patients. Soluble interleukin-2 receptor (IL2R) is a useful inflammatory marker and is seen to correlate with HLH disease activity. There is scarcity of data on IL2R in pediatric dengue patients with HLH. All patients (age < 18 years) with severe dengue confirmed by positive dengue IgM ELISA admitted to PICU were retrospectively enrolled. Patientswere screened for presence of HLH according to HLH 2004 criteria. Hemogram, ferritin, fibrinogen, liver, and renal function tests were noted. Patients who met four or more HLH criteria were treated with steroids and IL2R levels were sent to confirm the diagnosis of HLH. Out of 15 patients, nine patients met the criteria of HLH. IL2R levels were high in all HLH patients (mean 51,711, range 18,000–98,715 pg/mL). Mean ferritin levels were high in the HLH group as compared to non-HLH group (mean ferritin 34,593 vs. 3,206 ng/mL; p-value 0.004). Liver dysfunction was notably higher in the HLH group compared to non-HLH group (mean alanine aminotransferase 6,621 U/L vs. 165.6 U/L; p-value 0.04, mean aspartate aminotransferase 2,145 U/L vs. 104.2 U/L; 0.04, bilirubin level 4.2 mg/dL vs. 0.7 mg/dL; p-value 0.03). Four patients in the HLH group had acute kidney injury (AKI) and two required renal replacement therapy in the form of sustained low efficiency dialysis (SLED). Requirement for invasive ventilation was exclusively seen in HLH group and three patients developed ARDS. Two patients each in HLH and non-HLH group had shock requiring vasoactive therapy in addition to fluids. Mean days of ICU and hospital stay were higher in HLH group vs. non-HLH group but not statistically significant (6.4 vs. 4.4; p-value 0.32 and 8.44 vs. 5.6; p-value 0.18 days, respectively). All children in HLH group received steroids as per HLH protocol. In the HLH group, seven survived while two died. In the non-HLH group, all five patients survived. We concluded that IL2R levels are high in dengue HLH and useful for definitive diagnosis. Early recognition of this condition in severe dengue and prompt steroid therapy improves chances of better outcome.